Detection Tool for Authenticity and Nominal of Banknotes for the Blind Using Arduino Based Scanning Sensor - Eka Kiki Rachmawati; Dani Sasmoko (Journal of Technology Informatics and Engineering, 2023)
Money is a tool used to carry out buying and selling transactions and has been used by all humans in every corner of the world. This definitely makes money a basic commodity for everyone, even for people with disabilities such as the blind. The blind's limitations in seeing are a problem in terms of communication so they only rely on their sense of touch and hearing. The weakness of the blind in seeing and identifying money can cause money to be exchanged, taken wrongly, or even deceived by counterfeit money when buying and selling. Referring to this, it is necessary to have tools that can make it easier for the blind to identify the authenticity of money and the nominal value of money. The aim of this research is to design a tool that can be used to detect the authenticity of the nominal value of Rupiah banknotes. This tool uses a TCS3200-DB color sensor to detect the color of banknotes, then the microcontroller converts it into RGB data and outputs it in the form of sound output.and an ultraviolet sensor to detect the authenticity of money.The result of this research is that the system can recognize the authenticity and nominal value of moneypaper, especially rupiah. This makes it easier for users, especially the visually impaired, to carry out buying and selling transactions so they don't make mistakesto give or receive money.